LAN packet acquisition system using ARM based SBC - Naufal, Alee; Mostafijur, Rahman; R. Badlishah, Ahmad, Prof. Madya Dr.; Zahereel Ishwar, Abdul Khalib (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Kampus Pauh Putra, Perlis, Malaysia.